Corporate environmental responsiveness strategies: the importance of issue interpretation and organizational context - Sharma, Sanjay; Vredenburg, Harrie; Pablo, Amy L. (1998)
This article analyzes the environmental responsiveness strategies of seven companies in the Canadian oil industry over a 15-year period, during which environmental issues gained increasing public and regulatory attention. These within-industry corporate case comparisons serve as the basis for developing an understanding of corporate environmental responsiveness that centers on the relationships between issue interpretations and strategic responses as well as the role of antecedent organizational context elements. - Reproduced
Keywords: Petroleum industry